Mechanical and high pressure tribological properties of nanocrystalline Ti(N,C) and amorphous c: h nanocomposite coatings - Constantinides, Georgios; Tsotsos, Chrysostomos; Polychronopoulou, Kyriaki (My University, 2010)
This paper reports on the mechanical and high pressure tribological properties of nanocrystalline (nc-) Ti(N,C)/amorphous (a-) C:H deposited, using low temperature (∼ 200 °C) DC reactive magnetron sputtering. The mechanical properties are affected by the nc-Ti(N,C)/a-C:H phase fraction ratio. For increasing C contents (from 31 to 47 at.%) an increase of the a-C:H phase content and a degradation of the nanocrystalline phase occurs leading to a reduction in nanoindentation hardness (H) values (from 15 to 9 GPa) and reduced modulus (Er) values (from 150 to 80 GPa). A strong correlation between H/E ratio and wear performance was exhibited by the coatings. The synthesized coatings survived up to 100 m sliding distance when tested using pin-on-disc sliding configuration at > 4.5 GPa contact pressures and the measured friction coefficient values were similar for all films (μ ∼ 0.21–0.25).
Keywords: Tribology; Friction; Coatings; Nanocomposites (Materials)